Effect of water depth on the performance of solar still - Mohd Nurul Akhyar, Mohd Azlan (2017)
Water is an important element for a human to be healthy and energetic as it will effect human daily life. Clean water in the world is decreasing at a fast rate due to the rapid growth of industrialization and increasing population. In the future, human has to depend on other water source that can be get easily in large quantity, which is sea water. One of the method to overcome water shortage problem is water purification by using solar still. Solar still is one of the method that can change sea water or brackish water to pure water. This research uses a modified solar still that has magnifying lens, copper as the heat transfer agent, aspirator pump, temperature indicator and basin that coated with black paint. Sea water and tap water is chosen as the sample. The sample was poured into the basin with an area of 0.25m2 with 3 different depth of water level, which are 3cm, 2cm and 1cm. The experiments were repeated twice for each depth of water level. The experiment was conducted for 18 days, starts from 8am to 6pm. The value of pH, salinity, total dissolved solid and conductivity is taken after each of the experiment end. The data obtained shows that the pure water produced increases as the depth of water level in the basin decreases. The data also shows that untreated tap water is not safe for consumption. However, the treated tap water and sea water is safe for consumption.